PREDICTING OLDER ADULTS’ PHYSICAL RESILIENCE TO HEALTH STRESSORS: TEST PARADIGMS FOR THE FUTURE - Whitson, H E (Innov Aging, 2018)
Physical resilience, defined as one’s ability to withstand or recover from functional decline following an acute or chronic health stressor, is a concept that resonates with older patients and providers. Predicting an individual’s likelihood of a successful response to a given stressor would inform medical decision-making and help target resources. In August 2015, the National Institute on Aging convened a workshop to outline research needs to improve measures to predict and assess resilience in human aging (Hadly EC et al, J Gerontol A Biol Sci Med Sci 2017. 72(7): 980–990). One need that was identified was feasible clinical tests, such as simulation tests, to predict and assess resilient responses to “real world” stressors. This session, moderated by NIA Program Officers, will present several test paradigms currently under study as predictors of physical resilience to common stressors. Each test quantifies the individual’s response to a certain perturbation (e.g., vaccine, anesthesia, change of position) for the purpose of predicting future recovery from a health stressor. First, the moderators will introduce the emerging conceptual framework of physical resilience, emphasizing the dynamic nature of physiologic responses to stressors and their role in maintaining or regaining normal homeostasis and function. Brief presentations will follow on active lines of research, linked through the NIA-funded Physical Resiliencies: Indicators and Mechanisms in the Elderly (PRIME) Collaborative. Each speaker will describe a clinical test paradigm which is employed before, during, or soon after a stressor and will present data on the test’s ability to predict physical resilience.